Oxidative stress and antioxidant diet supplementation in ageing, atherosclerotic and immune dysfunction processes - MIQUEL, J; RAMÍREZ-BOSCÁ, A (Ars Pharmaceutica (Internet), 2004)
The increase in longevity in the developed countries requires costly health and social aid programs, since many elderlypersons suffer from pathological ageing processes linked to chronic degenerative diseases and long-lasting functionaldeficiencies. However, many studies have suggested that a greater number of persons could prevent pathological ageingby consuming diets rich in antioxidants. Such diets could provide the organism with more effective protection againstthe oxidative stress that contributes to normal ageing, and have an even more important role in atherosclerosis, immunedepression and other degenerative processes that are often found in pathological ageing.In accordance with these concepts and with the data reviewed, diet supplementation in mature or advanced age subjectswith antioxidants (such as thioproline, N-acetylcysteine and the phenolic compounds of curcuma longa) could increasethe chances of preventing or retarding the above-mentioned degenerative processes, thus helping to reach greaterlongevity with the adequate preservation of functional capacity